Hubungan Self Care dengan Kualitas Hidup Pasien TB Paru di RSU Mitra Sejati - Trisna Feberwati Laia; Sunarti Sunarti; Nadia Safira Fonna; Raudhatul Khairi. MR; Maria Fransisca Situmorang (Universitas Malahayati Lampung, 2025)
ABSTRACT TB disease suffered by someone will have an impact on society and if left unchecked will also have an impact on state revenues. This disease will also take up a person's productive time. The purpose of this study was to determine the relationship between self-care and the quality of life of pulmonary TB patients at Mitra Sejati General Hospital. The type of research used is an analytic descriptive survey with a Cross Sectional design. The population in this study were all patients with pulmonary TB disease at Mitra Sejati General Hospital, totaling 250 people. The subject retrieval technique used purposive sampling as many as 159 people. The instrument used in this study was a questionnaire to measure self care and quality of life of pulmonary TB patients. Analysis of research data is univariate and bivariate analysis with chi square test. The results of the study explained that the Self Care of pulmonary TB patients at Mitra Sejati General Hospital, most of the respondents had a good level of self care with a total of 78 respondents (49%), the Quality of Life of TB patients at Mitra Sejati General Hospital, most of the respondents had a good quality of life of TB patients with a total of 104 respondents (65%), and there was a relationship between Self Care and Quality of Life of Pulmonary TB Patients at Mitra Sejati General Hospital using Chisquare obtained a significance degree of p = 0.000. The conclusion of this study is that there is a relationship between Self Care and the Quality of Life of Lung TB Patients at Mitra Sejati General Hospital using Chisquare obtained a significance degree of p = 0.000. It is recommended to provide education to patients and families regarding the importance of proper self-care such as understanding of TB treatment, ways to maintain personal and environmental hygiene, and healthy lifestyles that contribute to improving their quality of life. Keywords: Self Care, Quality of Life, Pulmonary TB ABSTRAK Penyakit TB yang diderita seseorang akan berdampak kepada masyarakat dan apabila dibiarkan akan berdampak pula kepada pendapatan negara. Penyakit ini juga akan menyita wakti produktif seseorang. Tujuan penelitian ini adalah untuk mengetahui Hubungan self care dengan kualitas hidup pasien TB paru di RSU Mitra Sejati. Jenis penelitian yang digunakan adalah survei bersifat deskriptif analitik dengan rancangan Cross Sectional. Populasi dalam penelitian iniadalah seluruh pasien dengan penyakit TB paru di RSU Mitra Sejati sebanyak 250 orang. Teknik pengambilan subjek menggunakan purposive sampling sebanyak 159 orang. Instrumen yang digunakan dalam penelitian ini adalah kuesioner untuk mengukur self care dan kualitas hidup pasien TB paru. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan Self Care pasien TB paru di RSU Mitra Sejatisebagian besar responden memiliki tingkat self care yang baik dengan jumlah 78 responden (49%), Kualitas HidupPasien TB di RSU Mitra Sejati sebagian besar responden kualitas hidup pasien TB yang baik dengan jumlah 104 responden (65%), dan Ada hubungan Self Care Dengan Kualitas Hidup Pasien TB Paru Di RSU Mitra Sejati menggunakanChisquare diperoleh derajat signifikansi sebesar p= 0,000. Kesimpulan penelitian ini adalah ada hubungan Self Care Dengan Kualitas Hidup Pasien TB Paru Di RSU Mitra Sejati menggunakan Chisquare diperoleh derajat signifikansi sebesar p= 0,000. Disarankan untuk Pemberian edukasi kepada pasien dan keluarga mengenai pentingnya self care yang tepat seperti pemahaman tentang pengobatan TB, cara-cara menjaga kebersihan diri dan lingkungan, serta pola hidup sehat yang berkontribusi pada peningkatan kualitas hidup mereka. Kata Kunci: Self Care, Kualitas Hidup, TB Paru